Graph theory-based reaction pathway searches and DFT calculations for the mechanism studies of free radical-initiated peptide sequencing mass spectrometry (FRIPS MS): a model gas-phase reaction of GGR tri-peptide. Issue 9 (19th February 2020) - Lee, Jae-ung; Kim, Yeonjoon; Kim, Woo Youn; Oh, Han Bin
Abstract : A new approach for elucidating gas-phase fragmentation mechanisms is proposed: graph theory-based reaction pathway searches (ACE-Reaction program) and density functional theory (DFT) calculations. Abstract : Graph theory-based reaction pathway searches (ACE-Reaction program) and density functional theory calculations were performed to shed light on the mechanisms for the production of [ a n + H] +, x n +, y n +, z n +, and [ y n + 2H] + fragments formed in free radical-initiated peptide sequencing (FRIPS) mass spectrometry measurements of a small model system of glycine–glycine–arginine (GGR). In particular, the graph theory-based searches, which are rarely applied to gas-phase reaction studies, allowed us to investigate reaction mechanisms in an exhaustive manner without resorting to chemical intuition. As expected, radical-driven reaction pathways were favorable over charge-driven reaction pathways in terms of kinetics and thermodynamics. Charge- and radical-driven pathways for the formation of [ y n + 2H] + fragments were carefully compared, and it was revealed that the [ y n + 2H] + fragments observed in our FRIPS MS spectra originated from the radical-driven pathway, which is in contrast to the general expectation. The acquired understanding of the FRIPS fragmentation mechanism is expected to aid in the interpretation of FRIPS MS spectra. It should be emphasized that graph theory-based searches are powerful and effective methods for studying reaction mechanisms, including gas-phase reactions in mass spectrometry.